MANAJEMEN PEMBELAJARAN KETERAMPILAN VOKASIONAL ANAK TUNAGRAHITA RINGAN DI SLB KOTA BANDUNG - Setiawati, Andini (Wali Pikir: Journal Of Education, 2023)
This research was conducted to determine the management of skills programs in schools. Management is a process consisting of a series of activities; planning, organizing, mobilizing and supervising. The aim of this research is to get an overview of planning, implementation, evaluation, obstacles and efforts in vocational programs. The research method and approach is descriptive qualitative using observation, interview and documentation study techniques. As for the research results in planning, the school principal and teachers work together to create a vocational program, starting with determining the goals to be achieved, choosing materials, methods and media as outlined in the RPP. The implementation of learning has gone well even though the results have not been optimal. In learning evaluation, the aim is to find out the extent to which children understand the material, the teacher has carried out an evaluation even though he has not done it optimally, the obstacles that exist in implementation arise due to the lack of function of the school principal, vocational teachers, limited skills space, curriculum, not yet having assessment instruments. interests and talents, lack of cooperation between parents and teachers, lack of cooperation with business owners. Efforts to overcome the obstacles that exist in vocational learning by providing training or courses to teachers, seeking information about interest and talent assessments, school principals and teachers are starting to actively seek information and collaborate between parents and business owners